Building’s Constructions and Structures. Part I. The Classification of Buildings by Supporting Structures - Lámer, Géza (International Journal of Engineering and Management Sciences, 2017)
In the paper we deal with the structures interpreted among the buildings constructions. In the present, first part we classify the buildings constructions by their functions. Two main groups can be formed. Analysing supporting construction group can be shown that the building can be well classify by supporting constructions. The classification based on vertical supporting constructions like wall and column gives fourelement classification: wall frame, column frame, mixed frame and frame without vertical supporting constructions. This classification is very simple. Take into consideration of the buildings technology of walls and columns there can be given a classification whit more elements. Different subgroups can be interpreted using connections of walls and columns with floor construction in the certain groups.